Environment and Security
XVI, 225 p.
Keywords: This book is based on a conference addressing the relationship between the environment and security in the post-Cold War world. It brings together scholars and practitioners from a variety of different disciplines and perspectives in an effort to both explore the complexities of the relationship between environmental variables and security conditions, and re-focus the debate within the environmental community. The book combines analytical frameworks and case study material with proposals for addressing environmental challenges and enhancing the security and welfare of peoples, states and regions.